2011
DOI: 10.1021/es201850n
|View full text |Cite
|
Sign up to set email alerts
|

Polybrominated Diphenyl Ethers vs Alternate Brominated Flame Retardants and Dechloranes from East Asia to the Arctic

Abstract: Marine boundary layer air and seawater samples taken during a polar expedition cruise from East China Sea to the Arctic were analyzed in order to compare the occurrence, distribution, and fate of the banned polybrominated diphenyl ethers (PBDEs) with their brominated alternatives as well as the chlorinated Dechloranes. The sum of PBDEs (∑10PBDEs) in the atmosphere ranged from 0.07 to 8.1 pg m–3 with BDE–209 being the dominating congener and from not detected (n.d.) to 0.6 pg L–1 in seawater. Alternate brominat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

17
98
6

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 131 publications
(121 citation statements)
references
References 49 publications
17
98
6
Order By: Relevance
“…PUF was precleaned using soxhlet with Hexane/DCM (1:1) during 24 h, and QMA filters were precombusted for 4 h at 450 °C. Once the samples were taken, PUFs were packed using aluminium GD1 GD2 GD3 GD4 GD5 GD6 GD7 GD8 GD9 GD10 ) for PCBs, estimated from the gas-and dissolved-phase concentrations from this study and those reported in Gioia et al 11 and (b) air-to-water fugacity ratios (log(f A f W − 1 )) for other hydrophobic organic pollutants in high productivity regions from the north Atlantic and Arctic ocean [33][34][35] . For all these hydrophobic chemicals, there is a strong disequilibrium between air and water (high f A f W − 1 ) consistent with the role of the biological pump lowering water column concentrations of organic compounds.…”
Section: Methodsmentioning
confidence: 95%
“…PUF was precleaned using soxhlet with Hexane/DCM (1:1) during 24 h, and QMA filters were precombusted for 4 h at 450 °C. Once the samples were taken, PUFs were packed using aluminium GD1 GD2 GD3 GD4 GD5 GD6 GD7 GD8 GD9 GD10 ) for PCBs, estimated from the gas-and dissolved-phase concentrations from this study and those reported in Gioia et al 11 and (b) air-to-water fugacity ratios (log(f A f W − 1 )) for other hydrophobic organic pollutants in high productivity regions from the north Atlantic and Arctic ocean [33][34][35] . For all these hydrophobic chemicals, there is a strong disequilibrium between air and water (high f A f W − 1 ) consistent with the role of the biological pump lowering water column concentrations of organic compounds.…”
Section: Methodsmentioning
confidence: 95%
“…However, as passive air samplers show many advantages to active air samplers, such as no electricity requirement, low cost and simple construction, they have also been used to collect airborne DP (Klánová et al, 2008;Ren et al, 2008;Yu et al, 2015). XAD-2 resin and polyurethane foam (PUF) have been individually used for DP monitoring at a regional and global scale (Baek et al, 2013;Hoh et al, 2006;Ma et al, 2011;Möller et al, 2010Möller et al, , 2011Peverly et al, 2015;Ren et al, 2008;Sverko et al, 2010a). A low sampling rate, commonly 0.5 m 3 d −1 was recommended for DP relative to POPs substances (3-5 m 3 d −1 , Shoeib and Harner, 2002) when using PUF disk sampling deployment since only the fine/ultrafine fraction can enter the sampling chamber and be collected on the PUF disk (Klánová et al, 2008;Ren et al, 2008;Sverko et al, 2010a).…”
Section: Sample Collectionmentioning
confidence: 99%
“…SE and PLE (including ASE) were applied to solid samples, while LLE and SPE (e.g., C18) were used for liquid sample extraction . Mixed organic solvents, such as n-hexane/ acetone (v/v: 1/1) (Hoh et al, 2006;Ismail et al, 2009;Peverly et al, 2015;Ren et al, 2008;Salamova et al, 2014;Zhang et al, 2011a, b), n-hexane/dichloromethane (v/v: 1/1) (De la Möller et al, 2010Möller et al, , 2011Zhang et al, 2013), and the same mixtures with different proportions (Kang et al, 2010;Tomy et al, 2008;Wu et al, 2010;Xian et al, 2011), were commonly used for extraction.…”
Section: Sample Extraction and Clean-upmentioning
confidence: 99%
See 1 more Smart Citation
“…To meet the stringent fire safety regulations, several non-regulated HFRs, e.g., Dechlorane Plus (DP), decabromodiphenyl ethane (DBDPE), 1,2-bis(2,4,6-tribromophenoxy) ethane (BTBPE), 2,3,5,6-tetrabromo-p-xylene (PTBX), hexabromobenzene (HBB), pentabromoethylbenzene (PBEB), and pentabromotoluene (PBT), are considered to be the alternatives for the restricted or discontinued HFRs in some applications (Covaci et al, 2011;de Wit et al, 2010). Although studies on the environmental behavior of the alternative HFRs (AHFRs) are scarce, the limited information demonstrated that, analogous to the regulated HFRs, these AHFRs may also be toxic, persistent, bioaccumulative, and subject to long-range transport with global scale significance (de Wit et al, 2006;Möller et al, 2011;Wu et al, 2011).…”
Section: Introductionmentioning
confidence: 99%